2018
DOI: 10.1080/17476348.2018.1483724
|View full text |Cite
|
Sign up to set email alerts
|

How close are we to definitively identifying the respiratory health effects of e-cigarettes?

Abstract: Use of electronic cigarettes (e-cigarettes) is frequently promoted as a less harmful alternative to cigarette smoking. The impact of repeated inhalation of e-cigarette aerosols on respiratory health is not well understood. Areas covered: Using results from laboratory, observational, and clinical studies, we synthesize evidence relevant to potential respiratory health effects that may result from inhalation of e-cigarette aerosols. Expert commentary: Chemical analyses reveal that e-cigarette aerosols contain nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 62 publications
1
27
0
Order By: Relevance
“…E-cigarette is a device to heat and vaporise a liquid mixture that contains nicotine, propylene glycol, glycerin and flavourings to generate an aerosol inhaled by the users 5. Chemical analysis of e-cigarettes aerosols identified respiratory irritants and toxicants, regular exposures to which are associated with impaired respiratory functioning 6 7. Our recent study on effects of e-cigarettes flavouring chemicals on inflammatory and oxidative response using human monocytic cell lines showed biologically significant inflammatory response due to e-cigarette flavouring chemicals,8 9 providing plausibility for the association.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…E-cigarette is a device to heat and vaporise a liquid mixture that contains nicotine, propylene glycol, glycerin and flavourings to generate an aerosol inhaled by the users 5. Chemical analysis of e-cigarettes aerosols identified respiratory irritants and toxicants, regular exposures to which are associated with impaired respiratory functioning 6 7. Our recent study on effects of e-cigarettes flavouring chemicals on inflammatory and oxidative response using human monocytic cell lines showed biologically significant inflammatory response due to e-cigarette flavouring chemicals,8 9 providing plausibility for the association.…”
Section: Introductionmentioning
confidence: 97%
“…Asthma and chronic obstructive pulmonary disease are the most common causes of recurrent wheezing 14. Several studies have focused on associations of e-cigarettes use with wheezing or whistling and reported mixed results 7–9 12 15–23. One study on 2086 Southern California Children’s Health Study adolescent participants found e-cigarettes use increased risks of chronic bronchitis symptoms in teens while no significant association of e-cigarettes use with wheeze were found in teens after adjusting for cigarettes use 21.…”
Section: Introductionmentioning
confidence: 99%
“…Quitting smoking at the soonest opportunity is the best action a person can take to improve their health in the medium to long-term (3). Given that most of the 8 million smoking-related deaths projected to occur globally by 2030 will be among current, not prospective smokers (4), developing new effective ways of helping people to quit smoking is a public health imperative.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst it is widely accepted that e-cigarettes are substantially less harmful than combustible cigarettes, nevertheless these devices are not risk or harm free. Along with the uncertainty regarding the health impact of long term e-cigarette use concerns have also been raised as to more immediate cardio vascular and other health harms that have been linked to e-cigarette use (3,4). Whilst recognizing that complete cessation of all tobacco and nicotine use is the best action smokers can take to improve their health, the Royal College of Physicians and Public Health England have both indicated the likely benefit of those smokers who are either unable or unwilling to quit smoking combustible tobacco products to consider switching to using non-tobacco nicotine products.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst it is widely accepted that e-cigarettes are substantially less harmful than combustible cigarettes, nevertheless, these devices are not risk or harm-free. Along with the uncertainty regarding the health impact of long-term e-cigarette use, concerns have also been raised as to more immediate cardiovascular and other health harms that have been linked to e-cigarette use [ 6 , 7 ]. Although it is widely acknowledged that the complete cessation of all tobacco and nicotine use is the best action that smokers can take to improve their health, the Royal College of Physicians and Public Health England have both indicated the likely benefit of switching to the exclusive use of vaping devices for those smokers who are unable or unwilling to quit smoking combustible tobacco products.…”
Section: Introductionmentioning
confidence: 99%